Didactic device for teaching the importance of the time-dependent model for heat transfer calculations in constructive systems of buildings. (September 2022) - Ramírez-Zúñiga, Guillermo; Barrios, Guillermo; Huelsz Lesbros, Guadalupe; Sattele, Vanessa
There is a worldwide effort aimed at reducing energy consumption in buildings. Part of this effort includes bioclimatic design in the curricula for architects and engineers. The selection of constructive systems for the building envelope according to the climate is of significant importance for bioclimatic design. This has to be done by calculating the heat transfer through the constructive system using the time-dependent model. However, because the time-dependent model is easier to use it is also more commonly employed. To contribute to the teaching of the importance of using the time-dependent model, a didactic device and a practice were proposed. This paper presents the physical problem and the heat transfer models; the didactic device's design process, its components and operating method; as well as the methodology for the practice. The didactic device and practice were created by the interaction of experts and students who gave their opinions and suggestions during different workshops.